The Battle of Zango - Boyd, Jean (Evan Brothers Ltd, 1971)
The story of the Battle of Zango is based on a true story told to me by Mallam Sale- the same Mallam Sale who accompanied Uwargida when she went to see her husband at the East Gate.
Keywords: Collection of Stories; Juvenile Fiction; Realistic